The Effect of Dental Paste with Herbal Content on Remineralization and the Imaging with Fluorescent Technique in Teeth with White Spot Lesion - ILGIN, CAN; TAĞTEKİN, DİLEK; ALKAN, ELİF; YANIKOĞLU, FUNDA (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: To evaluate the effect of Gumgumix herbal toothpaste on remineralization of white spot lesions with a laser fluorescent system called FluoreCam. It is a pilot study. Methods: The FluoreCam system was used for the fluorescence imaging of the fifteen teeth with white spot lesions. During the study, the patients continued to use the previously owned toothpastes, addition to Gumgumix. Gumgumix was applied on the lesion area with a finger pressure twice a day and was not rinsed mouth after, only a limited spit and was prevented from taking any fluid during 30 minutes. The Compare option in the FluoreCam system was used to differentiate the situation before and after the use of the paste; if the marked area were yellow No Change; blue Sound Surface; green Improving; light blue Mild Improving and red meant Worsening. Results: Of the 13 lesions that were Suspect Surface initially, 46% were identified as Mild Improving, 7% as Moderate Worsening, 30% as No Change, and 15% as Sound Surface. Two of the white spot lesions were recovered totally as 100%. Conclusion: After use of Gumgumix for one week, remineralization was observed on teeth with white spot lesion. The white spot lesions on two teeth were totally healed.
Keywords: Remineralization; Herbal toothpaste; White spot lesion; Laser fluorescence; ESSENTIAL OIL; CARIES; GINGER